PMO-213 A prospective, randomised study of double-balloon colonoscopy vs conventional colonoscopy for technically difficult colonoscopy. (28th May 2012) - Despott, E J; Murino, A; Bourikas, L A; Nakamura, M; Fraser, C
Abstract : Introduction: Technically "difficult" (TD) colonoscopy may lead to incomplete colonoscopy, increased patient discomfort and potentially higher sedation dose. Parameters which are associated with TD colonoscopy include female gender, age, BMI, history of major pelvic/abdominal surgery or chronic constipation and previous failed conventional colonoscopy (CC). Double-balloon colonoscopy (DBC) may facilitate TD colonoscopy. Methods: We performed a prospective, randomised study comparing DBC and CC for TD colonoscopy. Patients referred for a colonoscopy were screened for parameters predictive of TD colonoscopy using a scoring system developed at our institution. Only patients with scores ≥3 qualified for recruitment; patients were then randomised to DBC or CC, performed by 1 of 2 designated experienced endoscopists. Collected data included patient pain/discomfort, difficulty of colonoscopy as judged by the endoscopist, sedation dose, colonoscopy completeness, time taken for caecal intubation/procedure completion and recovery time. On recovery, patients were asked to rate their satisfaction and whether they would opt to undergo the same type of colonoscopy in future. Results: Forty-four patients were recruited (DBC, n=22; CC, n=22). Median calculated pre-procedure difficulty scores were the same for both groups (4.0 vs 4.0, p=0.16). Mean patient discomfort and pain scores were significantly lower for the DBC group (2.6 vs 4.8, p=0.004 and 2.4 vs 4.9, p=0.002, respectively). Median doses of midazolam and pethidine used were significantly lower for DBC procedures (0 vs 1.25 mg, p=0.023 and 0 vs 25 mg, p=0.014, respectively). While differences in mean times taken for caecal intubation at DBC vs CC were similar (17.5 vs 14 min, p=0.18), DBC facilitated total colonoscopy in all 22 cases whereas 6 CC procedures were only completed with the aid of a magnetic endoscopic imager (MEI), required after a mean of 15 min of failing to progress. Another 3 CC cases failed to achieve caecal intubation despite use of a MEI and even a paediatric colonoscope. Median recovery time was significantly shorter for DBC (5 vs 20 min, p=0.014). Endoscopists found DBC to be significantly easier to perform than CC (median difficulty VAS: 3.6 vs 6.6 p=0.0005) and significantly more patients in the DBC group were satisfied (DBC vs CC median Likert satisfaction score: 5.0 vs 3.0, p=0.006). All patients in the DBC group said they would have DBC again but 41% of patients in the CC group said they would consider an alternative procedure instead. Conclusion: Our study suggests that DBC is a more comfortable and easier alternative to CC for TD cases. Since it appears to require less use of sedation, recovery also appears to be faster, with higher patient satisfaction levels. Competing interests: E J Despott: Grant/Research Support from: Fujifilm & Imotech Medical (UK), A Murino: Grant/Research Support from: Fujifilm & Imotech Medical (UK), L Bourikas: None declared, M Nakamura: None declared, C Fraser: None declared.